2021
DOI: 10.1039/d1cc04687j
|View full text |Cite
|
Sign up to set email alerts
|

Si-Bridged annulated BODIPYs: synthesis, unique structure and photophysical properties

Abstract: Two novel Si-bridged meso-annulated BODIPY dyes have been prepared through the intermolecular C-I silylation and subsequent intramolecular C-H silylation in one-pot reaction. Marked redshift of the main spectral bands are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Conjugated organoboron complexes containing N–B–N, O–B–O, or N–B–O bridges with five-, six-, and seven-membered core rings have played important roles in both fundamental studies and light-guiding applications, such as noninvasive bioimaging, molecular sensing, optoelectronic devices, and information display. In particular, tetracoordinate boron­(III) compounds with bidentate chelating ligands have been in the focus of these efforts owing to their rich and unique properties. The boron complexation increased rigidity of target compounds and was often accompanied by significantly increased chemical stability and photostability and high fluorescence quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated organoboron complexes containing N–B–N, O–B–O, or N–B–O bridges with five-, six-, and seven-membered core rings have played important roles in both fundamental studies and light-guiding applications, such as noninvasive bioimaging, molecular sensing, optoelectronic devices, and information display. In particular, tetracoordinate boron­(III) compounds with bidentate chelating ligands have been in the focus of these efforts owing to their rich and unique properties. The boron complexation increased rigidity of target compounds and was often accompanied by significantly increased chemical stability and photostability and high fluorescence quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…Our group devised β-silicon meso -aryl-fusion BODIPY dyes 8 using a one-pot chemical reaction consisting of intermolecular carbon–iodine silylation reaction and consequent intramolecular carbon–hydrogen silylation reaction (Scheme 5). 24 Interestingly, 8 has a distorted BODIPY core owing to long silicon–carbon bonds and the bulkiness of the silicon atom. Insertion with silicon leads to a large redshift of maximum absorption band and fluorescence band of 56 nm and 69 nm in contrast with the classic BODIPY, respectively, which is attributed to the efficient conjugation between σ* orbitals of silicon atom and π* orbitals of the framework.…”
Section: Zig-zag-fused Bodipysmentioning
confidence: 99%
“…7,8 In particular, intensive research on silicon-bridged biaryls, such as benzosiloles, [9][10][11][12] has demonstrated to be effective because they usually feature high electron transport, improved thermal stability, and outstanding photoluminescence properties. 13 Deep insights into benzosiloles revealed that the incorporation of silicon atoms into p-conjugated systems could considerably lower the lowest unoccupied molecular orbital (LUMO) energy levels via the distinctive s*-p* conjugation. [14][15][16][17][18] In addition, benzosilole derivatives have shown superior potential to the conventional fluorescent dyes in bio-imaging and fluorescent imaging technologies.…”
Section: Introductionmentioning
confidence: 99%